Diagnosis: From classification to prediction. (September 2019) - Armstrong, David
Abstract: Over the last two decades diagnostic labels have increasingly been sub-divided based on molecular and genetic 'signatures'. But this emphasis on disease sub-types defined in molecular terms, elides the central role of population-based predictive technologies in determining these new diagnoses. While molecular diagnostic sub-types might flow from the laboratory, the clinical validity of every putative diagnostic category must ultimately be tested against its predictive powers. In effect, the former logic of prognosis following diagnosis is reversed. This paper explores the emergence of this new method of diagnostic practice over the last half century. Highlights: Disease prognosis was embedded in the natural history of the diagnostic label. The relationship of diagnosis to prognosis has now been reversed. Prognosis increasingly determines diagnostic sub-types. The basis of diagnostic sub-types derives from population-based prediction.